Public administration reform in Jordan: concepts and practices - Jreisat, Jamil E. (2018)
This study reviews the transition of Jordan from a British colony to a modern independent state. It covers contextual attributes influencing the development of the administrative system such as centralization, demographic explosion, low economic growth, excessive reliance on patronage in recruitment for public positions, and corruption. These and other factors hinder administrative reform efforts. As case analysis illustrates, administrative decision making is non-institutional, regularly undermines the merit system, indifferent to accountability, and manifests a low commitment to professional ethics. The study emphasizes that administrative reform in Jordan needs to reconcile these obstacles and to advance skilled and ethical organizational leaders. - Reproduced.
Keywords: Public administration - Reform